Tuberculosis in children. (December 2016) - Velayati, Ali Akbar
Abstract: Tuberculosis (TB) is the main cause of infection-related death in the world. Children make up ∼5–15% of all TB cases. Severe forms of disease such as meningitis and disseminated form are more common in children. Due to current estimates of World Health Organization (WHO) in 2015, one million children suffer from TB around the world; of these, it is estimated that more than 136, 000 die a year. One study estimated 67 million children with latent TB which develops to active form with the rate of ∼850, 000 each year. The main way of entrance of tuberculosis in children is the respiratory tract. By contrast to adults, the majority of children with tuberculosis are not infectious to others. Usually children with TB do not have dominant signs or symptoms. Most common primary symptoms in children are cough and low grade fever. In some rare situations children present with a flu-like syndrome which recover within a week. The most common type of TB disease in children is pulmonary form. A total of 25–35% of cases of TB have an extra pulmonary manifestation. Disseminated TB (Miliary TB and TB meningitis) particularly occurs in young children <3 years old. Depending on the age of onset, physical and clinical manifestations would be different in children. In infants due to small airways we can see clinical manifestations such as nonproductive cough and mild dyspnea. In some cases failure to thrive is represented. Significant signs and symptoms are most common in preschool and adult patients. Half of school-age close contact children with radiographically moderate to severe pulmonary TB, have no symptoms or physical findings. In tuberculosis infection, the child has a positive tuberculin test but no clinical and radiological signs or symptoms. However, enlarged lymph nodes can be seen in rare cases. Depending on the position of the node these findings can be detected: partial or complete obstruction, segmental atelectasis, endobronchial tuberculosis and fistulous tract, collapse consolidation, segmental lesion, pericarditis, or tracheoesophageal fistula. Early morning gastric lavage is the best sample for diagnosis of pulmonary TB in a child. Gastric aspirates are used in children younger than 6 years instead of sputum. In <50% of cases Mycobacterium tuberculosis are detected in three gastric aspirates. The aim of the BCG vaccination is to prevent life threatening tuberculosis in children such as meningitis and disseminated TB. The rate of miliary TB and meningitis are higher in neonates. They are also more disposed to progression to disease. Development to disease between 5 years and 10 years is rare. Atypical forms of TB present in children with AIDS. In conclusion most cases of tuberculosis in children occur within 1 year of the infection, tuberculosis disease in a child shows recent transmission of the organism.